Selênio na biofortificação e no estresse oxidativo induzido por fungicidas na cultura da soja - Mahl, Gabriel Augusto dos Reis (2024)
The application of selenium to plants, known for its antioxidant and nutritional properties, in conjunction with a fungicide mixture, seeks not only to control diseases but also to enhance the nutritional quality and productivity of the soybean crop, offering an innovative approach to improving sustainable agriculture. This study evaluated the influence of selenium application associated with commercial fungicide mixtures to increase productivity and biofortification in soybeans. The work was carried out in two stages on an agricultural property located in the municipality of Cascavel-PR. In the first experiment, the effect of applying doses of selenium (0, 10, 20, 40, and 80 g.ha-1) to plants of two soybean cultivars at the R1 stage on productivity and oil and protein content was evaluated. The experimental design was randomized blocks in a double factorial scheme (Selenium x Cultivar) with three replications. The second experiment analyzed the effect of selenium doses (0, 40, and 80 g.ha-1) associated with different types of fungicide applied at the R1 stage. The experimental design was randomized blocks in a double factorial scheme with three replications. The following variables were evaluated: leaf area index; normalized difference vegetation index; number of pods per plant; yield in kg.ha-1; oil and protein content of the grains; thousand-seed weight (TSW); germination percentage, seed vigor, and selenium content in the grains obtained after harvest. The results of the first experiment showed an effect of the dose of Se on grain yield regardless of the cultivar used, with the use of 80 g.ha-1, resulting in a decrease in the magnitude of this variable. In the second experiment, the yield, TSW, and protein content variables significantly responded to the variation in the selenium dose factor, with the selenium dose of 40 g.ha 1 being the maximum, followed by a drop in both responses. The fungicide/selenium dose interaction was significant for seed germination and vigor, with fungicide A associated with 40 g.ha-1 of Se, increasing both variables. The leaf area index changed according to the dose of Se applied, with the use of 80 g.ha-1 causing a decrease in leaf area after applying selenium. As for its seed content, the application of 80 g.ha-1 resulted in a more significant increase than 40 g.ha-1, which also differed from the control. Finally, the use of selenium associated with fungicide mixtures promotes changes in leaf area indices, seed physiology, and productivity in soybeans, and the use of 40 g.ha-1 of this element is ideal for maximizing the expression of these variables. For biofortification, the use of 80 g.ha-1 of selenium promotes a more relevant increase in this mineral element in soybean seeds when compared to 40 g.ha-1 .